Furfural aniline epoxy monomer, furfural aniline epoxy resin and preparation method of furfural aniline epoxy monomer and furfural aniline epoxy resin

By using furfural as raw material, furfural-based aniline epoxy monomer with biepoxy groups was prepared and reacted with other monomers to construct an epoxy resin with excellent thermal stability and flame retardant properties, which solved the problem of current There are safety hazards and low biobase content during the preparation of epoxy resin.

CN119431338AActive Publication Date: 2025-02-14CHINA PETROLEUM & CHEMICAL CORP +1

Patent Information

Application Number
CN202310939706.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-07-28
Publication Date
2025-02-14
Estimated Expiration
2043-07-28

Smart Images

  • Figure CN119431338A_ABST
    Figure CN119431338A_ABST
Patent Text Reader

Abstract

The invention discloses a furfural aniline epoxy monomer, furfural aniline epoxy resin and a preparation method thereof. The furfural aniline epoxy monomer has the following structure: # imgabs0: 4-hydroxyaniline and 2-furaldehyde are subjected to a Schiff base reaction, an obtained Schiff base intermediate is subjected to a hydrogenation reduction reaction, and a secondary amine intermediate is obtained; carrying out substitution reaction on the secondary amine intermediate and epoxy chloropropane to obtain a furfural aniline epoxy monomer, and carrying out ring-opening addition on the furfural aniline epoxy monomer, a DOPO (9, 10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide)-based epoxy monomer and diaminodiaryl sulfone to obtain the flame-retardant epoxy resin with relatively good thermal stability and excellent flame retardance. The flame-retardant epoxy resin can be widely applied.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a furfural aniline epoxy resin monomer and a furfural aniline epoxy resin, and also relates to a preparation method of the furfural aniline epoxy resin monomer and the epoxy resin, belonging to the technical field of polymer materials. Background Art

[0002] Epoxy resins usually have excellent solvent resistance, good chemical stability and mechanical strength, and they account for the largest share in the construction industry and the coating industry. In addition, functional epoxy resin oligomers are also widely used in aerospace and electronic products. Epoxy resin monomers and prepolymers usually refer to an organic component containing multiple epoxy units. The epoxy groups in the molecular structure further react with the curing agent to form a corresponding polymer system. The most common system with the largest market share is the epoxy glycidyl ether (DGEBA) system using bisphenol A as the raw material, but the disadvantage is that the structure and composition of epoxy vary greatly with the differences in the preparation process, and the product performance varies greatly. Therefore, the performance of the product is also affected to a certain extent.

[0003] Traditional DGEBA is mainly prepared with bisphenol A and acetone as raw materials, but the participation of acetone components in the preparation process leads to major safety issues in the preparation process, especially for high temperature environments, there are inevitable hidden dangers of flammability and explosion. Therefore, the construction of corresponding alternative raw materials can effectively avoid the safety hazards in the derivation process of bisphenol A. It is worth noting that the bio-based content of epoxy resin with DGEBA as raw material is extremely low. Therefore, increasing the corresponding bio-based content and establishing the corresponding epoxy resin construction process can effectively improve the social and economic value of the corresponding products. Furfural, as a decomposition product of agricultural and sideline products, has the typical advantages of a wide range of sources and is less affected by the geographical environment. The bio-based chemicals converted from it can reflect better added value and better utilization efficiency of biomass resources.

[0004] At present, the construction method of bio-based epoxy monomers is gradually being improved. Using furfural as raw material, research on basic process conditions is carried out to further explore the characteristics of its corresponding epoxy resin polymer. In-depth research on the physicochemical properties and functional characteristics of epoxy resin materials is also one of the current directions for the development of material applications, especially the construction of epoxy structures with low saponified chlorine content (<100ppm), which is also an important indicator of current electronic-grade epoxies. In addition, based on epoxy monomers constructed from furfural, the establishment of corresponding flame-retardant polymer preparation methods is also of great positive significance, and is expected to be widely used in many research fields such as coatings, adhesives, aerospace materials, and electronic and electrical industries. Summary of the invention

[0005] In view of the technical problems existing in the prior art, the first object of the present invention is to provide a furfural aniline epoxy monomer (EP-Fulap for short), which introduces a diepoxy group and can further construct an epoxy resin through ring-opening polymerization. The monomer has a lower viscosity and a low saponification chlorine value, and belongs to an electronic grade epoxy grade. Compared with the existing petroleum-based epoxy resins, the epoxy resin constructed using the furfural aniline epoxy monomer introduces a furan structure to increase the biomass content of the material, and at the same time introduces an aniline group, which is beneficial to the improvement of the thermal stability of the epoxy resin.

[0006] The second object of the present invention is to provide a method for preparing furfural aniline epoxy monomer, which uses bio-based furan formaldehyde as a raw material, has a wide source and is renewable, and the preparation method is simple, the conditions are mild, and it can be industrially produced.

[0007] The third object of the present invention is to provide a furfural aniline epoxy resin, which has good thermal stability and excellent flame retardant properties and can be widely used as a flame retardant functional epoxy resin.

[0008] The fourth object of the present invention is to provide a method for preparing furfural aniline epoxy resin. The synthesis steps of the epoxy resin material are simple and the raw material sources are wide, which is conducive to large-scale production.

[0009] In order to achieve the above technical objectives, the present invention provides a furfural aniline epoxy monomer having a structure of Formula 1:

[0010]

[0011] The EP-Fulap of the present invention is a light yellow liquid, with a viscosity of η=168mP·s (300r / min) at 25°C, a volatile matter of less than 0.195%, and a saponification chlorine value of 0.00936%.

[0012] The furfural aniline epoxy monomer of the present invention has two epoxy groups and can be used with other monomers to construct epoxy resins. It has an electronic grade epoxy grade and has greater advantages than existing petroleum-based epoxy resins. The furfural aniline epoxy monomer contains both furan groups and aniline groups, which is beneficial to improving the thermal stability of the epoxy resin.

[0013] The present invention also provides a method for preparing a furfural aniline epoxy monomer, which comprises the following steps:

[0014] 1) 4-hydroxyaniline reacts with 2-furancarboxaldehyde via a Schiff base reaction to obtain a Schiff base intermediate of formula 2;

[0015] 2) The Schiff base intermediate is subjected to hydrogenation reduction reaction to obtain a secondary amine intermediate of formula 3;

[0016] 3) the secondary amine intermediate reacts with epichlorohydrin through substitution reaction to obtain furfural aniline epoxy monomer;

[0017]

[0018] As a preferred embodiment, 4-hydroxyaniline and 2-furaldehyde are reacted in a polar solvent under acidic conditions at a temperature of 10 to 30° C. for 18 to 30 hours. The reaction can be carried out under air atmosphere. The acidic conditions are achieved by adding an organic acid, such as formic acid. The amount of formic acid used is 2% to 8% of the molar amount of 2-furaldehyde, preferably 3% to 5%. The reaction temperature is further preferably reacted at room temperature of 20 to 30° C. The reaction time is further preferably 20 to 26 hours.

[0019] As a preferred solution, the polar solvent can be selected from low-carbon alcohols, such as C1-C5 alcohols, and specifically methanol and / or ethanol. The amount of the polar solvent is such that the concentration of 2-furancarboxaldehyde is 0.8-1 mmol / mL, preferably 0.9-0.92 mmol / mL.

[0020] As a preferred solution, the molar ratio of 4-hydroxyaniline to 2-furancarboxaldehyde is (0.9-1.1): 1. The Schiff base reaction generally reacts relatively completely, and 4-hydroxyaniline and 2-furancarboxaldehyde can preferably react in a stoichiometric ratio of 1:1.

[0021] As a preferred solution, the Schiff base intermediate reacts with the hydrogenation reducing agent in a protic solvent at a temperature of -5 to 5°C for 2 to 8 hours. The most preferred reaction temperature is 0°C, and the most preferred reaction time is 4 to 5 hours.

[0022] As a preferred solution, the protic solvent is at least one of methanol, ethanol and water. The amount of the protic solvent is intended to ensure that the concentration of the Schiff base intermediate is 0.05 to 0.15 g / mL, preferably 0.1 to 0.11 g / mL.

[0023] As a preferred solution, the hydrogenation reduction reagent includes at least one of sodium borohydride, sodium cyanoborohydride, and sodium triacetoxyborohydride, and more preferably sodium borohydride.

[0024] As a preferred solution, the molar ratio of the hydrogenation reduction agent to the Schiff base intermediate is (0.5-1.5): 1. The molar ratio of the hydrogenation reduction agent to the Schiff base intermediate is most preferably 0.8-1.2:1.

[0025] As a preferred solution, the secondary amine intermediate and epichlorohydrin are first reacted at 75-85°C for 2-8 hours under the action of a phase transfer catalyst; then the temperature is lowered to room temperature, an alkaline solution is added, and the reaction is stirred for 15-45 minutes. In the reaction process, epichlorohydrin serves as both a solvent and a reaction raw material. The stirring speed of the stirring reaction is 600-1000 rpm. The most preferred reaction time of the stirring reaction is 25-35 minutes.

[0026] As a preferred embodiment, the phase transfer catalyst includes tetrabutylammonium bromide.

[0027] As a more preferred solution, the molar ratio of the phase transfer catalyst to the secondary amine intermediate and epichlorohydrin is (0.15-0.25):1:(15-25).

[0028] As a preferred solution, the alkaline solution includes at least one of potassium carbonate solution, sodium carbonate solution, sodium hydroxide solution and potassium hydroxide solution.

[0029] As a preferred solution, the mass concentration of the alkaline solution is 20% to 50%.

[0030] As a preferred embodiment, the molar ratio of the alkaline component to the secondary amine intermediate in the alkaline solution is (2-6):1.

[0031] The present invention also provides a method for preparing a furfural aniline epoxy resin, wherein the furfural aniline epoxy monomer is subjected to a melting and curing reaction with a DOPO-based epoxy monomer having a structure of formula 4 and a diaminodiaryl sulfone to obtain a product;

[0032]

[0033] The DOPO-based epoxy monomer (EP-DOPO for short) of the present invention can be purchased directly (CAS: 102486-95-3) or synthesized according to the prior art. The infrared spectra of EP-DOPO are as follows: Figure 7 shown.

[0034] The diaminodiaryl sulfones of the present invention include but are not limited to 4,4'-diaminodiphenyl sulfone, and the structural formula is as follows:

[0035]

[0036] As a preferred embodiment, the molar ratio of the sum of the epoxy groups in the furfural aniline epoxy monomer and the DOPO epoxy monomer to the NH bonds in the diaminodiaryl sulfone is (0.8-1.5):1;

[0037] As a preferred solution, the molar ratio of the furfural aniline epoxy monomer to the DOPO-based epoxy monomer is (1.5-15): 1. The ratio of the furfural aniline epoxy monomer to the DOPO-based epoxy monomer can adjust the phosphorus content in the epoxy resin. When the ratio of the DOPO-based epoxy monomer increases, the flame retardancy of the epoxy resin will be significantly improved, while when the ratio of the furfural aniline epoxy monomer is low, the stability of the reduced resin will be affected to a certain extent.

[0038] As a preferred solution, the melting temperature is 100-180°C. The preferred melting temperature is 105-120°C.

[0039] As a preferred solution, the curing reaction conditions are: temperature of 190-220° C., time of 2-5 hours. A further preferred curing reaction temperature is 200-210° C., and a further preferred curing reaction time is 2-3 hours.

[0040] The invention also provides a furfural aniline epoxy resin, which is obtained by the preparation method.

[0041] The furfural aniline epoxy resin provided by the present invention has the following structural formula (the following structural formula is only used as a typical structure for illustration):

[0042]

[0043] Furfural aniline epoxy resin is composed of three units: A, B, and C; wherein the structural units of A, B, and C are respectively:

[0044]

[0045] Among them, it can be seen from the above structural formula that the structural unit A and the structural unit C are connected to the structural unit B through CN respectively; wherein, there is no specific requirement for the connection order of the structural unit A and the structural unit C; specifically, the structural unit B is a diaminodiaryl sulfone curing agent unit, which has two amino groups and four connection sites, and can be connected to the structural unit A and / or the structural unit C respectively, and can be arbitrarily interspersed. The molar ratio between the structural unit A and the structural unit C can be regulated in the range of (1.5-15):1.

[0046] The furfural aniline epoxy resin of the present invention has an initial decomposition temperature of 340-360° C. (preferably 345-355° C.) and a maximum decomposition temperature of 400-420° C. (preferably 405-415° C., most preferably 408-412° C.).

[0047] The furfural aniline epoxy resin of the present invention is completely extinguished 40 seconds after leaving the fire source, more preferably 30 seconds, further preferably 20 seconds, further preferably 10 seconds, and most preferably 5 seconds.

[0048] The mass content of phosphorus in the furfural aniline epoxy resin of the invention is controlled within the range of 0.5% to 5%.

[0049] Compared with the prior art, the technical solution of the present invention has the following beneficial technical effects:

[0050] (1) The EP-Fulap preparation process provided by the present invention has a simple process flow, mild conditions, and a high degree of greenness, and is a highly safe epoxy monomer.

[0051] (2) The EP-Fulap provided by the present invention has a lower viscosity, is easy to use, is easy to mix materials efficiently, and has a low saponification chlorine value, belonging to the electronic grade epoxy grade, which has greater advantages than the existing petroleum-based epoxy resin.

[0052] (3) The epoxy polymer constructed by EP-Fulap, EP-DOPO and diaminodiaryl sulfone provided by the present invention has the characteristics of good thermal stability and excellent flame retardant properties, and can be widely used as a flame retardant functional resin.

[0053] (4) The main monomer 2-furan carboxaldehyde used in the synthesis process of EP-Fulap of the present invention is a bio-based raw material obtained by converting or separating biomass such as corn cobs. It is a renewable resource with high biological added value and good biosafety.

[0054] (5) The furfural aniline epoxy resin of the present invention has simple synthesis steps, and the raw material sources are wide, the product has high biological safety, and the prepared epoxy resin has excellent heat resistance and good flame retardant properties, which has greater advantages than the existing petroleum-based epoxy resin. BRIEF DESCRIPTION OF THE DRAWINGS

[0055] Figure 1 The reaction pathway for the synthesis of EP-Fulap.

[0056] Figure 2 This is the actual appearance of EP-Fulap.

[0057] Figure 3 This is the hydrogen NMR spectrum of EP-Fulap.

[0058] Figure 4 This is the carbon NMR spectrum of EP-Fulap.

[0059] Figure 5 This is the high-resolution mass spectrum of EP-Fulap.

[0060] Figure 6 This is the Fourier infrared spectrum of EP-Fulap.

[0061] Figure 7This is the Fourier infrared spectrum of EP-DOPO.

[0062] Figure 8 This is the Fourier infrared spectrum of the furfural aniline epoxy resin in Example 4.

[0063] Fig. 9 This is the Fourier infrared spectrum of the furfural aniline epoxy resin in Example 5.

[0064] Fig.10 This is the Fourier infrared spectrum of the furfural aniline epoxy resin in Example 6.

[0065] Fig.11 This is the TGA diagram of the furfural aniline epoxy resin in Example 4.

[0066] Fig.12 This is the TGA diagram of the furfural aniline epoxy resin in Example 5.

[0067] Fig.13 This is the TGA diagram of the furfural aniline epoxy resin in Example 6.

[0068] Fig.14 This is a combustion test diagram of furfural aniline epoxy resin in Example 4.

[0069] Fig.15 This is a combustion test diagram of furfural aniline epoxy resin in Example 5.

[0070] Fig.16 This is a combustion test diagram of furfural aniline epoxy resin in Example 6. DETAILED DESCRIPTION

[0071] The experimental methods described in the following examples are conventional methods unless otherwise specified; the reagents and materials described are commercially available unless otherwise specified.

[0072] Example 1

[0073] Preparation of compound a (see Figure 1 ):

[0074] 4-Hydroxyaniline (20 g, 0.1834 mol) was added to a 500 mL round-bottom flask, and ethanol (200 mL) was added. 2-furancarboxaldehyde (17.47 g, 0.1818 mol) was slowly added under stirring (1000 rpm), and an appropriate amount of formic acid (0.335 g, 0.0073 mol) was added dropwise. After completion, the reaction was stirred at room temperature for 24 h, and the reaction progress was monitored by thin layer chromatography. After the reaction was completed, it was filtered with a Buchner funnel, and the filter cake was washed with an appropriate amount of ethanol (60 mL) and a small amount of ethyl acetate (20 mL), and then the filter cake was placed in a vacuum drying oven under negative pressure to obtain a brown-gray solid powder, namely compound a (33.5 g), with a yield of 98.5%.

[0075] 1 H NMR(400MHz, DMSO-d6)δ9.52(s,1H),8.42(s,1H),7.90(d,J=1.7Hz,1H),7.24–7.10 (m,2H),7.05(dd,J=3.5,0.7Hz,1H),6.84–6.72(m,2H),6.68(dd,J=3.5,1.8Hz,1H).

[0076] Example 2

[0077] Preparation of compound b (see Figure 1 ):

[0078] Compound a (26.6 g, 0.1422 mol) prepared in Example 1 was added to a 500 mL round-bottom flask, and 250 mL of methanol was added to completely dissolve it. If necessary, dissolution was assisted by ultrasound. Sodium borohydride (5.38 g, 0.1422 mol) was added at 0°C. Sodium borohydride was added four times within 1 hour, and then stirred to react for 4 hours. The reaction progress was monitored by thin layer chromatography. After the reaction was completed, 50 mL of distilled water was added to quench the reaction. The reaction solution was extracted with ethyl acetate (120 mL) three times, dried with anhydrous sodium sulfate, and then the solvent was removed by rotary evaporation. The obtained solid was placed in a vacuum drying oven and dried to obtain a pink to brownish red solid compound b (26.47 g, 0.14 mol) with a yield of 99%.

[0079] 1 H NMR (400MHz, DMSO-d6) δ8.44(s,1H),7.54(d,J=1.8Hz,1H),6.51(q,J=9.0Hz,4H),6.3 6(t,J=2.5Hz,1H), 6.24(d,J=3.1Hz,1H), 5.38(t,J=6.3Hz,1H), 4.13(d,J=6.1Hz,2H).

[0080] Example 3

[0081] Preparation of EP-Fulap (see Figure 1 ):

[0082] At room temperature, epichlorohydrin (245 g, 2.64 mol) and tetrabutylammonium bromide (8.5 g, 0.0264 mol) were added to a 500 mL round-bottom flask. Compound b (25 g, 0.1322 mol) was slowly added while stirring. The mixture was quickly stirred to mix. The temperature of the reaction system was then raised to 80°C and the reaction was stirred for 6 h. After the reaction is completed, the reaction system is cooled to room temperature, and a sodium hydroxide aqueous solution (30%, 21.2g NaOH+50g H2O) is slowly added dropwise using a constant pressure low liquid funnel. After stirring for 30 minutes, an appropriate amount of distilled water is added to dilute the reaction solution, and ethyl acetate is extracted. After drying with anhydrous sodium sulfate, the solvent is removed by rotation, and the furfural aniline epoxy resin monomer EP-Fulap (25.57g) is purified with a yield of 64.24%. The product is a light yellow liquid with a viscosity of η=300r / min 168mP·s, a volatile matter of <0.195%, and a saponification chlorine value of 0.00936%. The physical appearance is as follows Figure 2 As shown, the NMR mass spectrum Figures 3-4 As shown in the high-resolution mass spectrometry Figure 5 As shown, infrared Figure 6 shown.

[0083] 1 H NMR(400MHz, CDCl3)δ7.32(d,J=1.7Hz,1H),6.88–6.75(m,4H),6.27(dd,J=3.3,1.9Hz,1 H),6.13(d,J=3.2Hz,1H),4.44(s,2H),4.12(dd,J=11.1,3.2Hz,1H),3.87(dd,J=11.1,5 .6Hz,1H),3.56(dd,J=15.5,3.4Hz,1H),3.40–3.25(m,2H),3.18–3.05(m,1H),2.84(t,J =4.6Hz,1H),2.80–2.72(m,1H),2.70(dd,J=5.0,2.7Hz,1H),2.53(dd,J=5.0,2.7Hz,1H).

[0084] 13 C NMR (101MHz, CDCl3) δ152.33,151.27,143.67,141.91,115.75,115.35,110.27,107.67,69.55,53.13,50.77,50.33,49.12,45.46,44.72.

[0085] HRMS(ESI-TOF)m / z Calcd for[M+H] + :302.1387,found:302.1395.[M+Na] + :324.1206,found:324.1214.[M+K] + :340.0946,found:340.0951.

[0086] Example 4

[0087] Furfural aniline epoxy resin EP-Fulap (0.64 g, 0.00212 mol) was weighed into a reaction flask, and curing agent 4,4'-diaminodiphenyl sulfone (0.398 g, 0.0016 mol) and epoxy resin EP-DOPO (0.47 g, 0.00108 mol) were added at 25°C under air atmosphere, and the temperature was raised to 110°C and stirred rapidly for 30 min to ensure that the materials were fully melted. After mixing evenly, the above materials were evenly poured on a metal template, moved into a curing box with a nitrogen atmosphere, and the temperature was slowly raised to 200°C for curing for 2 h. The mixture was naturally cooled under a nitrogen atmosphere to obtain a furfural aniline epoxy resin polymer.

[0088] Thermogravimetric data analysis under nitrogen, such as Fig.11 As shown, the initial decomposition temperature is 351°C, the maximum decomposition temperature is 408°C, and the obtained material has good heat resistance.

[0089] In the combustion experiment, Fig.14 The combustion conditions of the polymer were observed 5 seconds after being ignited by an open flame. In this combustion test, the flame of the polymer went out immediately after the fire source left. The inability to burn without an open flame indicated that the polymer had very good flame retardant properties.

[0090] By judging its infrared data, such as Figure 8 As shown, the infrared peak of ethylene oxide (914 cm -1 ) disappears, indicating that the epoxy groups and amine groups of the epoxy resin have been completely polymerized.

[0091] Polymer infrared data attribute: 1038cm -1 Vibration of carbon-oxygen bond in CO; 1230cm -1 Stretching vibration of the COC bond in the furan ring; 1595, 1509, 1449 cm -1 Benzene ring peak: 1104.5cm -1 It is the carbon-oxygen characteristic peak of 2°ROH generated by epoxy ring opening; 3417cm -1 The strong and broad absorption peak at is the peak formed by the appearance of -OH group after the ring opening of ethylene oxide.

[0092] Example 5

[0093] Furfural aniline epoxy resin EP-Fulap (0.85 g, 0.00282 mol) was weighed into a reaction flask, and curing agent 4,4'-diaminodiphenyl sulfone (0.4167 g, 0.00168 mol) and epoxy resin EP-DOPO (0.234 g, 0.000537 mol) were added at 25°C under air atmosphere, and the temperature was raised to 110°C while rapidly stirring for 30 min to ensure that the materials were fully melted. After mixing evenly, the above materials were evenly poured on a metal template, moved into a curing box with a nitrogen atmosphere, and the temperature was slowly raised to 200°C for curing for 2 h. The mixture was naturally cooled under a nitrogen atmosphere to obtain a furfural aniline epoxy resin polymer.

[0094] Thermogravimetric data analysis under nitrogen, such as Fig.12 As shown, the initial decomposition temperature is 345°C, the maximum decomposition temperature is 412°C, and the obtained material has good heat resistance.

[0095] In the combustion experiment, Fig.15 The combustion conditions of the polymer were observed 5 seconds after being ignited by an open flame. In this combustion test, the flame of the polymer went out immediately after the fire source left. The inability to burn without an open flame indicated that the polymer had very good flame retardant properties.

[0096] By judging its infrared data, such as Fig. 9 As shown in the figure, the infrared characteristic peak of ethylene oxide (914 cm -1 The disappearance of the epoxy groups and amine groups of the epoxy resin indicates that they have been completely polymerized.

[0097] Polymer infrared data attribute: 1042cm -1 Vibration of carbon-oxygen bond in CO; 1221cm -1 Stretching vibration of the COC bond in the furan ring; 1594, 1509, 1455 cm -1 Benzene ring peak: 1104.4cm -1 It is the carbon-oxygen characteristic peak of 2°ROH generated by epoxy ring opening; 3405cm -1 The strong and broad absorption peak at is the peak formed by the appearance of -OH group after the ring opening of ethylene oxide.

[0098] Example 6

[0099] Furfural aniline epoxy resin EP-Fulap (0.956 g, 0.00317 mol) was weighed into a reaction flask, and curing agent 4,4'-diaminodiphenyl sulfone (0.427 g, 0.00172 mol) and epoxy resin EP-DOPO (0.1168 g, 0.00027 mol) were added at 25°C under air atmosphere, and the temperature was raised to 110°C while rapidly stirring for 30 min to ensure that the materials were fully melted. After mixing evenly, the above materials were evenly poured on a metal template, moved into a curing box with a nitrogen atmosphere, and the temperature was slowly raised to 200°C for curing for 2 h. The mixture was naturally cooled under a nitrogen atmosphere to obtain a furfural aniline epoxy resin polymer.

[0100] Thermogravimetric data analysis under nitrogen, such as Fig.13 As shown, the initial decomposition temperature is 355°C, the maximum decomposition temperature is 411°C, and the obtained material has good heat resistance.

[0101] In the combustion experiment, Fig.16 The combustion condition of the polymer was observed 5 seconds after being ignited by an open flame. In this combustion test, after the fire source left, the flame of the polymer became significantly smaller 2 seconds after burning and was completely extinguished 3 seconds later, indicating that the polymer has good flame retardant properties.

[0102] By judging its infrared data, such as Fig.10 As shown in the figure, the infrared characteristic peak of ethylene oxide (914 cm -1 The disappearance of the epoxy groups and amine groups of the epoxy resin indicates that they have been completely polymerized.

[0103] Polymer infrared data attribute: 1230cm -1 Stretching vibration of COC bond in furan ring; 1594,1508.8cm -1 Benzene ring peak: 1104.4cm -1 It is the carbon-oxygen characteristic peak of 2°ROH generated by epoxy ring opening; 3419cm -1 The strong and broad absorption peak at is the peak formed by the appearance of -OH group after the ring opening of ethylene oxide.

[0104] contrast Figures 14 to 16 It can be seen that when the phosphorus content in the epoxy resin is reduced to 2.2wt%, 1.1wt%, and 0.55wt%, respectively, it is obvious that Figures 14-15 Basically can't light it. Fig.16 It lights up and then goes out in about 2s, indicating that when the phosphorus content in the epoxy resin is above 0.55wt%, it has a good flame retardant effect. From the thermogravimetric decomposition data, it can be seen that with the increase of the EP-Fulap ratio, the 5% and 10% thermal weight loss rates of the epoxy resin decrease slightly.

[0105] The above is only a preferred embodiment of the present invention. It should be noted that, for those skilled in the art, several improvements and modifications can be made without departing from the principle of the present invention, and these improvements and modifications should also be considered as the protection scope of the present invention. All components not specified in this embodiment can be implemented by existing technologies.

Claims

1. A furfural aniline epoxy monomer, characterized in that: It has the structure of formula 1:

2. The method for preparing a furfural aniline epoxy monomer according to claim 1, characterized in that: The following steps are involved: 1) 4-hydroxyaniline reacts with 2-furancarboxaldehyde via a Schiff base reaction to obtain a Schiff base intermediate of formula 2; 2) The Schiff base intermediate is subjected to hydrogenation reduction reaction to obtain a secondary amine intermediate of formula 3; 3) the secondary amine intermediate reacts with epichlorohydrin through substitution reaction to obtain furfural aniline epoxy monomer; 3. The method for preparing a furfural aniline epoxy monomer according to claim 2, characterized in that: 4-Hydroxyaniline and 2-furancarboxaldehyde are reacted in a polar solvent under acidic conditions at 10-30°C for 18-30 hours.

4. The method for preparing a furfural aniline epoxy monomer according to claim 3, characterized in that: The polar solvent is methanol and / or ethanol.

5. The method for preparing a furfural aniline epoxy monomer according to claim 3, characterized in that: The molar ratio of the 4-hydroxyaniline to the 2-furancarboxaldehyde is (0.9-1.1):

1.

6. The method for preparing a furfural aniline epoxy monomer according to any one of claims 2 to 5, characterized in that: The Schiff base intermediate reacts with a hydrogenation reducing agent in a protic solvent at a temperature of -5 to 5°C for 2 to 8 hours.

7. The method for preparing a furfural aniline epoxy monomer according to claim 6, characterized in that: The protic solvent is at least one of methanol, ethanol and water.

8. The method for preparing a furfural aniline epoxy monomer according to claim 6, characterized in that: The hydrogenation reduction reagent includes at least one of sodium borohydride, sodium cyanoborohydride, and sodium triacetoxyborohydride.

9. The method for preparing a furfural aniline epoxy monomer according to claim 6, characterized in that: The molar ratio of the hydrogenation reduction reagent to the Schiff base intermediate is (0.5-1.5):

1.

10. The method for preparing a furfural aniline epoxy monomer according to any one of claims 2 to 5 and 7 to 9, characterized in that: The secondary amine intermediate and epichlorohydrin are first reacted at 75-85°C for 2-8 hours under the action of a phase transfer catalyst; then the temperature is lowered to room temperature, an alkaline solution is added, and the reaction is stirred for 15-45 minutes.

11. The method for preparing a furfural aniline epoxy monomer according to claim 10, characterized in that: The phase transfer catalyst comprises tetrabutylammonium bromide; The molar ratio of the phase transfer catalyst to the secondary amine intermediate and epichlorohydrin is (0.15-0.25):1:(15-25).

12. The method for preparing a furfural aniline epoxy monomer according to claim 10, characterized in that: The alkaline solution includes at least one of a potassium carbonate solution, a sodium carbonate solution, a sodium hydroxide solution, and a potassium hydroxide solution; The mass concentration of the alkaline solution is 20% to 50%; The molar ratio of the alkaline component to the secondary amine intermediate in the alkaline solution is (2-6):

1.

13. A method for preparing a furfural aniline epoxy resin, characterized in that: The furfural aniline epoxy monomer of claim 1 and the DOPO epoxy monomer of formula 4 and diaminodiaryl sulfone are reacted by melting and curing to obtain; 14. The method for preparing a furfural aniline epoxy resin according to claim 13, characterized in that: The molar ratio of the sum of the epoxy groups in the furfural aniline epoxy monomer and the DOPO epoxy monomer to the NH bonds in the diaminodiaryl sulfone is (0.8-1.5):1; The molar ratio of the furfural aniline epoxy monomer to the DOPO epoxy monomer is (1.5-15):

1.

15. The method for preparing a furfural aniline epoxy resin according to claim 13, characterized in that: The melting temperature is 100-180°C; The curing reaction conditions are: temperature of 190-220° C. and time of 2-5 hours.

16. A furfural aniline epoxy resin, characterized in that: Obtained by the preparation method according to any one of claims 13 to 15.

Citation Information

Patent Citations

  • DOPO type reactive flame retardant with terminal group as epoxy group, preparation method therefor and application thereof

    CN105061711A

  • Melamine-based nitrogen and phosphorus-containing compound, preparation method and application thereof, and flame-retardant epoxy resin composition of melamine-based nitrogen and phosphorus-containing compound

    CN112679545A

  • V-triazolyl-substituted stilbenes

    US3485831A

Cited By

  • Flame-retardant EPDM (ethylene-propylene-diene monomer) material for automobile wire harness and preparation method

    CN121825117A